Reforming the Tax System of Ukraine in the Context of Globalization Challenges - MALIARCHUK, Oleksii; RYLIEIEV, Serhii; SKRYPNYK, Mykola; MATSAK, Oleksii; KOLOMIIETS, Pavlo (Theoretical and Practical Research in Economic Fields, 2025)
The relevance of the study is due to the intensification of global challenges that exert multidimensional pressure on national tax systems. The purpose of the study is to elucidate the strategic pathways of reforming Ukraine’s tax system in light of the challenges posed by globalization. The study used a set of methods, in particular structural and logical analysis, comparative assessment of European countries’ tax parameters, and correlation analysis to identify relationships between tax, macroeconomic and digital indicators. It was found that an increase in the corporate income tax rate is accompanied by a decrease in the efficiency of taxation (r = -0.4439) alongside the increase in GDP losses (r = 0.4641), which indicates the stimulation of tax evasion. A strong relationship between the level of corruption and the gross domestic product per capita (r = 0.7307) was revealed, as well as an inverse relationship between the perception of corruption and the burden of taxation (r = -0.3816), which confirmed the corruption’s impact on fiscal discipline. The positive correlation of the income tax rate with digital development (r = 0.6090) and cybersecurity (r = 0.5873) indicates that countries with higher corporate taxes are investing more actively in digital transformation. The study revealed that Ukraine’s tax system is characterized by excessive administrative complexity, weak resilience to global challenges, a high share of the shadow economy and an insufficient level of digital integration. The conclusions substantiate the need for a comprehensive approach to tax reform, which combines deregulation, digitalization, the fight against corruption and bringing national legislation in line with the requirements of the EU and global tax initiatives. The scientific novelty of the study lies in a comprehensive approach to the examination of Ukraine’s tax system through the lens of global trends, while meticulously considering digital and macroeconomic parameters. This methodology facilitated the identification of profound interconnections between essential fiscal and socio-economic indicators, employing contemporary correlation analytics as its foundation. Prospects for further research involve the development of a model for an adaptive tax policy in Ukraine, which will facilitate a nimble response to external challenges.